Rice subsector development and farmer efficiency in Nepal: implications for further transformation and food security - Choudhary, Dyutiman; Banskota, Kamal; Khanal, Narayan Prasad; McDonald, Andrew J.; Krupnik, Timothy J.; Erenstein, Olaf (Frontiers Media, 2022)
With economic development agricultural systems in the Global South transform from subsistence farming to higher productivity with market integration and increase in rural income and food security. In Nepal, agriculture continues to provide livelihoods for two-thirds of the predominantly rural population, largely at a subsistence-level. Rice is the staple food and covers the largest land area but yields are relatively low, with an annual import bill of USD 300 Million. The study uses data from 310 households from two distinct rice producing areas to assess farmers' rice production systems. It analyses farmers' rice production efficiency using a stochastic frontier production function to suggest how to advance the transformation of Nepal's rice sector. Our study finds that while agriculture related services such as access to inputs, information, markets, irrigation, and finance have generally improved, paddy farmers are only able to achieve 76% of potential output. Small/marginal farms were relatively less efficient than medium and large farms. Women farmers faced unequal access to technologies and have lower productivity than men. Unavailability of labor and capital, land fragmentation, and the lack of consistent access to seed and fertilizers contribute to reduced efficiency. Public and private sector investments are needed to enhance the timely and adequate access to quality seeds, fertilizers, processing facilities, and equipment services. Adopting a market systems approach through cooperative farming, targeted delivery of extension services, and linkages with rice millers can promote inclusive growth and improve rice food security in Nepal.